(untitled) (Journal of Asian Development Studies, 2025)
This study examines the impact of financial grant loans on economic growth in Bangladesh, India, Pakistan, and Sri Lanka from 1981 to 2022. Using a mixed-method approach, the research analyses both quantitative and qualitative data to explore the relationship between financial grants and development. Various econometric tests suggest that grant loans make a significant contribution to GDP growth, although their effectiveness varies across countries. In Bangladesh, grants helped bridge the savings-investment gap through infrastructure and social services. India leveraged grants to support economic stability and growth. Pakistan benefited from grants through targeted policy actions, despite political and structural challenges. Sri Lanka primarily used grants for post-war reconstruction and infrastructure development. The study emphasises that country-specific factors—such as governance, institutional strength, and political stability—are crucial to maximising the impact of grants. Policy recommendations include improving institutional frameworks, ensuring political stability, targeting critical sectors, enhancing monitoring and evaluation, fostering regional cooperation, encouraging private sector involvement, and reducing long-term dependency. These findings offer practical guidance for policymakers and development practitioners in tailoring financial aid to specific national contexts. By adopting these strategies, South Asian countries can increase the effectiveness of grant loans and promote sustainable, inclusive economic growth.